Nepenthes mirabilis (Lour.) Druce Planlet at a Various Levels of Murashige & Skoog Medium Density In Vitro - Nadia Fakhriyati Arfa; Endang Nurcahyani; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
This study aims to determine the variation of the stomata index of the Kantong Semar (Nepenthes mirabilis) planlet at a various medium density of the Murashige and Skoog. This study used a Completely Randomized Design using one factor (medium density of the Murashige and Skoog). We used 5 levels of medium density, i.e.: 1/16 MS, 1/8 MS, 1/4 MS, 1/2 MS, and MS. Homogeneity test used Levene’s test of 5% significance level, then analysis of variance is carried out at 5% significance level and followed by Tukey test at 5% significance level. The results showed that the lower the level of Murashige and Skoog medium density on the Nepenthes mirabilis plantlet, the stomata index also increased.